Implementasi Speech Recognition Menggunakan API IBM Watson - Basit, Acep Abdul; Akbar, R. Reza El (INNOVATICS: International Journal on Innovation in Research of Informatics, 2021)
Lack of skill English is a major problem for someone who wants to learn to speak English in the pronunciation section. A person often feels insecure to speak English with other people even though in his own understanding it can be said to understand English. English learning applications, it can help to learn and practice good and correct pronunciation or pronunciation in English without having to involve other people. Using the Extreme Programming development method, it is found that the use of technology can be a solution for learning to speak English without having to be seen and valued by others. With the help of Speech Recognition, the process of recognizing a person's voice from a spoken phrase is the result that can be obtained. This English learning application is used to learn English spelling, so you can know how to pronounce English words and sentences properly and correctly.